Healing, Violence, and Native American Women - Ramirez, Renya K. (Social justice, 2004)
Part of a special issue on native women and state violence. The writer outlines a cultural approach to the healing of native women and others from the devastation of the American Indian Holocaust that involves the use of translation and transculturation. She describes a 1999 exhibit that translated colonial images of Indian women, explored their history and roles, and applied tribal spiritual practices to help participants recover from the effects of colonialism and the violence against native women that it condones.